Barriers to organisational development in higher education lifelong learning initiatives - Öhman, Peter; Jaldemark, Jimmy (Proceedings of the International Conference on Networked Learning, 2024)
From an economic human capital perspective, higher education lifelong learning initiatives should include the professional development of individuals as well as organisational development. This indicates the dissolving of boundaries between individual and organisational development and that successful professional development occurs at both individual and aggregated levels. Based on the networked mode, higher education institutions could be closely linked to their surrounding society, embracing a two-way relationship with a hybrid character, including multiple connections with branches and/or organisations. In such initiatives, formal education and informal work-related tasks are blurred and both are emphasised as equally important. In focus are collaborative features and the idea to link theoretical reasoning to authentic organisational problems. To offer higher education lifelong learning for organisational development, Mid Sweden University initiated a project called BUFFL in collaboration with eight organisations belonging to an established network of banks and insurance companies. This paper aims at reporting barriers to organisational development in higher education lifelong learning. It answers the following research question: Which barriers could be identified when implementing a hybrid and networked approach to higher education lifelong learning for organisational development? A case-study-inspired approach was conducted. In total, 328 registrations from the collaborating organisations were documented in the BUFFL courses. In addition to open-ended questions and Likert scale questions in the course evaluations, the methods also included conversations with leading representatives of the collaborating organisations. Although several barriers were highlighted in line with the innovation resistance theory, the main barrier seems to be that no organisation applied lifelong learning as a tool for strategic organisational development. The study suggests that a crucial barrier breaker to reduce or eliminate the main barrier is a course on strategically managed competence development for leading representatives of participating organisations. A combined focus on individuals and organisations could also stimulate leading representatives to take a holistic approach to the organisation’s competence development. This includes increased responsibility to ensure that investments in the competence area are beneficial for the organisation. Bringing company-relevant data as input to the courses could ensure the establishment of strong links between theoretical perspectives and work-related practices.